Leadership of Headmaster and Work Motivation in Elementary School Partner with Undergraduate Program at PGSD FKIP UNTAN - Mastar Asran (Universitas Tanjungpura, 2018)
This research aims to describe the relationship of school leadership to work motivation of teachers in primary school Partners PGSD Prodi S1 FKIP UNTAN District of South Pontianak Pontianak. The method used in this study is a correlation research method, forms of survey research. The results were obtained (1) Leadership Head Elementary School Guidance and Counseling Program Partners S1 PGSD UNTAN in the District of South Pontianak Pontianak City at 4.59 with criteria